Geração de eletricidade com Biogás: estudo de viabilidade em estação de tratamento de esgotos no Paraná - Moraes, Karl Haruo Kimura de (2020)
The distributed generation of electric energy produced from the use of organic waste is an alternative that needs to be carefully analyzed, due to the countless advantages associated with this process. Considering the all human activity consumes resources and in the end of this they become waste, we can classify urban sewage as highly polluting waste, and its treatment is necessary for the community and the environment, once it removes pollutants from the water previously used by the population, in order to return it to water bodies in good conditions and, if a controlled anaerobic process is used, biogas can be generated. Due to its high calorific value, biogas has the potential to be used as a primary source for electricity generation, thus requiring an evaluation of the economic feasibility of using generator engines for the use of biogas produced by Upflow Anaerobic Sludge Blanket reactors (UASB) already installed in sewage treatment plants. The survey of the Net Present Value (NPV), the Internal Rate of Return (IRR), the payback and the level cost of energy (LCOE) appear as appropriate tools to carry out such an assessment, having as reference the number of inhabitants that these stations can serve. The simulations were carried out using, as in the case of the study, the volume of treated sewage in some cities in the State of Paraná, based on the amount of population served by sewage, thus estimating the potential for biogas production in the stations and its potential for generating electricity. The proposed method was an appropriate tool to point out and demonstrate the use of biogas as an energy and beneficial resource, as verified by the result of the city of Curitiba, which obtained the NPV of 87,834,069.69 reais, an IRR of 18.04% am with a 5-month payback, as well as its Levelized Cost of Energy (LCOE) value of R $ 34.53 / MWh.